2001
DOI: 10.1074/jbc.m103944200
|View full text |Cite
|
Sign up to set email alerts
|

CCC1 Is a Transporter That Mediates Vacuolar Iron Storage in Yeast

Abstract: The budding yeast Saccharomyces cerevisiae can grow for generations in the absence of exogenous iron, indicating a capacity to store intracellular iron. As cells can accumulate iron by endocytosis we studied iron metabolism in yeast that were defective in endocytosis. We demonstrated that endocytosis-defective yeast (⌬end4) can store iron in the vacuole, indicating a transfer of iron from the cytosol to the vacuole. Using several different criteria we demonstrated that CCC1 encodes a transporter that effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
371
2
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 316 publications
(400 citation statements)
references
References 25 publications
(17 reference statements)
22
371
2
5
Order By: Relevance
“…The VIT1 domain is homologous to Arabidopsis VIT1, which is involved in transporting iron into vacuoles (Kim et al, 2006). The domain is also similar to yeast Ca 2+ -sensitive cross-complementer 1 (CCC1) protein, which is localized in vacuolar membranes, and is an iron/manganese transporter that transfers iron from the cytoplasm and into vacuoles (Li et al, 2001). Unlike the ferritins, very little is known about the Er-VIT1 family.…”
Section: Introductionmentioning
confidence: 99%
“…The VIT1 domain is homologous to Arabidopsis VIT1, which is involved in transporting iron into vacuoles (Kim et al, 2006). The domain is also similar to yeast Ca 2+ -sensitive cross-complementer 1 (CCC1) protein, which is localized in vacuolar membranes, and is an iron/manganese transporter that transfers iron from the cytoplasm and into vacuoles (Li et al, 2001). Unlike the ferritins, very little is known about the Er-VIT1 family.…”
Section: Introductionmentioning
confidence: 99%
“…This could occur through either through a direct reduction in cytosolic iron or by affecting the synthesis of iron-sulfur clusters in mitochondria, as the level of iron-sulfur clusters appears to regulate transcription of the iron-regulon (16). Our previous studies demonstrated that yeast store iron in the vacuole and that Ccc1p is a vacuolar protein that transports iron from the cytosol to the vacuole (15). Vacuoles isolated from ⌬mrs3⌬mrs4 cells showed an increase in iron content compared with vacuoles from wild type cells (Fig.…”
Section: Deletion Of Mrs3 and Mrs4 Increases Vacuolar Iron Accumulatimentioning
confidence: 99%
“…Iron Sensitivity of ⌬ccc1 by Reducing Cellular Iron Accumulation-Cells with a deletion in CCC1, which encodes a vacuolar iron and manganese transporter, are more sensitive to growth on high iron medium than wild type cells, presumably because of an inability to remove iron from the cytosol (15). We screened for genes that when overexpressed could suppress the high iron sensitivity of ⌬ccc1 cells.…”
Section: Overexpression Of Mrs3 or Mrs4 Suppressesmentioning
confidence: 99%
See 2 more Smart Citations